1998
DOI: 10.1021/bi9731450
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Active Site of Cytochrome P450 2B1:  Metabolism of 7-Alkoxycoumarins by the Wild Type and Five Site-Directed Mutants

Abstract: A series of 7-alkoxycoumarins (chain length of 1-7 carbon atoms) was utilized as active site probes of purified Escherichia coli-expressed cytochrome P450 2B1 wild type and five site-directed mutants (I114V, F206L, V363A, V363L, and G478S). The production of 7-hydroxycoumarin, the O-dealkylation product, by the wild-type enzyme exhibited a rank order of C2 > C4 > C3 > C1 > C5 > C6 = C7. The pattern observed for the P450 I114V mutant was similar to that of the wild-type enzyme, whereas with F206L and G478S muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…The resulting metabolite profile was remarkably similar to that of CYP2B1. Kobayashi et al (1998) observed that substitution of Val-363 with leucine in CYP2B1 almost abolished the production of 7-hydroxycoumarin and favored the production of 7-(3-hydroxybutoxy)coumarin. Our data revealed that the special metabolite ratio observed for CYP2B1 V363L is characteristic for CYP2B6.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The resulting metabolite profile was remarkably similar to that of CYP2B1. Kobayashi et al (1998) observed that substitution of Val-363 with leucine in CYP2B1 almost abolished the production of 7-hydroxycoumarin and favored the production of 7-(3-hydroxybutoxy)coumarin. Our data revealed that the special metabolite ratio observed for CYP2B1 V363L is characteristic for CYP2B6.…”
Section: Discussionmentioning
confidence: 97%
“…In several studies, 7-butoxycoumarin was found to be very informative as an active-site probe for CYP2B1, as this substrate can undergo regioselective hydroxylation on the side chain (Kobayashi et al, 1998;. Therefore, 7-butoxycoumarin allowed us to analyze the architecture of the active sites of CYP2B6 and CYP2E1 more carefully and was used at a concentration according to .…”
Section: Downloaded Frommentioning
confidence: 99%
“…Modeling and experimental techniques were used to investigate the effect of the chain length on the metabolism of a series of 7-alkoxycoumarins by P450 2B1 and its mutants (Kobayashi et al, 1998). The ability of the wild-type enzyme to oxidize a specific compound was found to depend upon the length of the alkyl chain.…”
Section: Liu Et Almentioning
confidence: 99%
“…In addition, site-directed mutagenesis was crucial to understand the structural and functional role of residues in the active site, access channel, and a recently observed peripheral pocket (Kobayashi et al, 1998;Hernandez et al, 2006;Jang et al, 2014Jang et al, , 2015. Our multifaceted approach has revealed how movement of secondary structure elements, such as the F-G helices and I helix, and reorientation of active-site residues, such as F206 and F297, allow CYP2B enzymes to bind compounds as small as a-pinene (molecular weight 5 136 g/mol) and as large as two molecules of amlodipine (molecular weight 5 409 g/mol) with high affinity.…”
Section: Introductionmentioning
confidence: 99%